2013
DOI: 10.1159/000355679
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion of Ibuprofen for Treatment of Patent Ductus Arteriosus in Very Low Birth Weight Infants

Abstract: Background: Ibuprofen (IBU) has proved as effective as indomethacin in the pharmacological closure of hemodynamically significant patent ductus arteriosus (HsPDA), with an efficacy inversely related to gestational age (57-89%). Objective: This study aimed to establish whether continuous infusions of IBU could be more effective in very low birth weight infants with no additional adverse effects and reduce the need for surgical ligation. Methods: A prospective, randomized, double-dummy study was conducted on 112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
0
16
1
3
Order By: Relevance
“…Early use of ibuprofen vs its use when PDA became significant resulted in a reduction in oxygen use of 2 days in the first 28 days after birth. A further study 64 compared bolus with continuous infusion of ibuprofen and reported a higher rate of sustained closure after continuous infusion (68% vs 86%, P = .03). However, no other neonatal outcomes were affected in any of these studies.…”
Section: Ibuprofenmentioning
confidence: 99%
“…Early use of ibuprofen vs its use when PDA became significant resulted in a reduction in oxygen use of 2 days in the first 28 days after birth. A further study 64 compared bolus with continuous infusion of ibuprofen and reported a higher rate of sustained closure after continuous infusion (68% vs 86%, P = .03). However, no other neonatal outcomes were affected in any of these studies.…”
Section: Ibuprofenmentioning
confidence: 99%
“…After the marketing authorisation, five small single centre trials, [19][20][21][22][23] two systematic reviews with meta-analyses, 24 25 and one observational study 26 were published. One of the trials found that continuous infusion of ibuprofen was more effective and just as safe as the bolus dose; in a second trial ibuprofen proved as effective as indomethacin, while in two trials paracetamol was as effective as ibuprofen but safer.…”
Section: Ibuprofenmentioning
confidence: 99%
“…Our proposed maintenance dosage of 4 mg kg −1 every 12 h, leads to comparable trough concentrations with 10 mg kg −1  day −1 every 24 h, but with 22% lower peak concentrations. Secondly, continuous ibuprofen administration has been shown to be more effective than intermittent by Lago et al [13] even without a loading dose, leading to 84 vs 64% PDA closure, respectively. The higher responsiveness following a more stable ibuprofen exposure is confirmed by the counterintuitive finding of higher closure rates following oral than intravenous administration, which is thought to be caused by the more graduate absorption following oral intake [36].…”
Section: Discussionmentioning
confidence: 99%